2022
DOI: 10.1155/2022/6372258
|View full text |Cite
|
Sign up to set email alerts
|

Financial System Design for High-Tech Enterprise Based on Cloud Service and Task Scheduling Algorithm

Abstract: So far, with the development of the network, a new era of cloud computing is gradually advancing. Cloud services based on cloud computing technology have long become a new business model with broad application prospects. This paper studies the design of a high-tech enterprise financial system based on cloud service and task scheduling algorithm. The project can fully meet the following requirements: the establishment of a financial management system can improve the degree of automation and computerization of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Regarding services based on cloud computing technology, Cai (2018) mentioned that, Cloud computing is the practice of using a network of remote servers hosted on the Internet to store, manage, and process data, rather than a local server or personal computer. Zhang et al, (2022) mentioned that these services have been being used for a long time and have become the new business model; various types of organizations with the aim of creating and sharing applications and resources can adopt its applicability. Moreover, Kaur and Bala (2021) when referring to cloud computing indicated that, it is a platform that offers a customizable infrastructure where applications can be configured prior to execution.…”
Section: Cloud Computing and Crowdfunding Platformmentioning
confidence: 99%
“…Regarding services based on cloud computing technology, Cai (2018) mentioned that, Cloud computing is the practice of using a network of remote servers hosted on the Internet to store, manage, and process data, rather than a local server or personal computer. Zhang et al, (2022) mentioned that these services have been being used for a long time and have become the new business model; various types of organizations with the aim of creating and sharing applications and resources can adopt its applicability. Moreover, Kaur and Bala (2021) when referring to cloud computing indicated that, it is a platform that offers a customizable infrastructure where applications can be configured prior to execution.…”
Section: Cloud Computing and Crowdfunding Platformmentioning
confidence: 99%